Analysis of Management of Educational Facilities and Infrastructure at Labang State Elementary School, Bangkalan Regency - Cahyani, Ridha Rahmah; Siswoyo, Andika Adinanda; Rania, Nabila Putri; Istiqomaturrobiah, Asri; Utami, Putri Puspita; Abdillah, Moh. Zulfan (JUPE : Jurnal Pendidikan Mandala, 2024)
This investigation was executed with the purpose of illustrating the orchestration of current resources at SDN Labang Bangkalan. The technique employed in this exploration is an interpretative qualitative investigation. The participants in this inquiry consist of the headmaster and the assistant principals, along with the educational blueprint for SDN Labang Bangkalan. From the findings of this exploration, it is understood that the coordination of assets and infrastructure at SDN Labang Bangkalan begins from the strategic formulation phase, aiming to maximize the utilization of available amenities. This is caused by facilities that are still lacking, so optimizing existing facilities is really needed.